Árvore de ECOS: Um Jogo para Ensino de Conceitos de Ecossistemas de Software - Ferreira, Thaís de Souza Deluca (2021)
Software Engineering (SE) has advanced in theoretical and applied research in order to meet the requirements of an increasingly competitive and dynamic market. Technological evolution and frequent changes in the development process together with industry experience bring challenges to the field. In this context, education institutions face difficulties in adapting themselves to this scenario and deal with a range of emerging topics in SE. New themes have emerged, such as software ecosystems (SECO), which has gained prominence in the industry and raised several researches to the field. Since it is a new scenario with several concepts that need to be taught and are not always trivial, it is important that the knowledge is passed in a clear and simple way and that the teaching-learning process is as attractive as possible. Therefore, since SE field has used educational games for a long time, but the SECO theme has not been explored in SE classes, this work presents a digital game to support the teaching of SECO concepts called SECO Tree. The game was built following the development process for educational games called ENgAGED and verified with students based on the use of MEEGA+ evaluation model. For the purpose of this study, the dimensions usability, challenge, satisfaction, fun, focused attention, relevance and perception of learning of the MEEGA + model were analyzed. Results showed that, in the students' perception, the game helps the teaching of SECO’s basic concept from the students’ perspective, being more attractive to those who do not play frequently, since the game focuses on simple mechanics and goals in order to avoid other barriers to the process.